A non-twisted layered metal wire and a preparation method thereof
By controlling the cold drawing deformation rate and lubrication method, the problem of twisting and delamination in metal wires has been solved, enabling the efficient production of twist-free metal wires. These wires are suitable for bridge cable steel wires, automotive tire radial wires, and diamond wire busbars used in photovoltaic silicon wafer cutting, thus improving production efficiency.
Patent Information
- Application Number
- CN202411443035.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Existing technologies cannot effectively control the deformation rate, which makes metal wires prone to torsion and delamination during cold drawing. This fails to meet the torsional performance requirements of engineering applications such as bridge cable steel wire, automobile tire radial wire, and diamond wire busbars used for photovoltaic silicon wafer cutting, thus hindering the improvement of production efficiency.
By controlling the cold drawing deformation rate, selecting high-carbon steel wire as raw material, and using dry or wet multi-pass cold drawing methods within different diameter ranges, lubricating with soap powder or emulsion, and adjusting the single-pass elongation coefficient and drawing die half-angle, the deformation rate is ensured to be within a specific range, thus suppressing torsional delamination.
It effectively avoids twisting and delamination, improves production efficiency by at least 2.5 times, and is suitable for diamond wire busbars used in bridge cable steel wire, automobile tire radial wire, and photovoltaic silicon wafer cutting. It is also simple to operate and does not increase processing difficulty.
Smart Images

Figure CN118957427B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal wire processing, and in particular to a torsion-free layered metal wire and a preparation method thereof. The metal wire can be a bridge cable steel wire, an automobile tire meridian, and a diamond wire busbar for photovoltaic silicon wafer cutting. Background Art
[0002] Pearlite steel wire has high strength and good toughness, and is widely used in the fields of long-span bridge cables, automobile tire radials and diamond wires. As an important engineering material, pearlite steel wire is mainly produced by cold drawing technology. When cold-drawn pearlite steel wire is used in the above fields, it will be subjected to complex alternating stresses. Therefore, in addition to meeting the basic strength requirements, it must also meet the corresponding torsional performance requirements, especially no torsional delamination.
[0003] In recent years, researchers have conducted extensive research to avoid torsional delamination in cold-drawn pearlite steel wire.
[0004] In the prior art, the patent (CN105483556B) discloses a strengthening method for producing high-strength bead wire materials and a preparation method for bead wire: reducing the carbon content in the raw materials, adding Cr elements that can refine the pearlite lamellae, to improve the work hardening rate, inhibit cementite dissolution during cold drawing, and solve the torsional delamination phenomenon of bead wire with a strain of 3.0≥ε≥2.3. However, this method has certain limitations and is not suitable for bridge cable wires and diamond wire busbars that require higher carbon content.
[0005] The patent (CN103785704B) discloses a method for preparing an ultra-high strength steel wire that is resistant to torsion delamination and has excellent fatigue performance: the compression rate of the last wet-drawn wire is controlled below 2%, so that the steel wire undergoes a slight drawing deformation in the last pass, improving the stress state inside the steel wire, thereby improving the torsion performance of the cold-drawn steel wire and the fatigue life of the steel wire. However, the method described in which the compression rate of the last pass is controlled below 2% cannot achieve the correction effect on the wire ring diameter, which is not applicable to the diamond wire busbar with extremely high ring diameter requirements.
[0006] The patent (CN106111726A) discloses a method for producing high-strength and high-torsion performance galvanized steel wire for bridge cables: the finished galvanized steel wire is cooled and drawn by immersion in a water tank and then stabilized, the deformation is controlled at 8%~15%, and the drawing speed is ≤2.5m / s, so that the number of torsion turns of the galvanized steel wire meets the requirements of bridge cable manufacturing. However, the 8%~15% cold drawing deformation of the steel wire after galvanizing will inevitably cause damage to the galvanized layer, which will significantly reduce the protective effect of the galvanized layer on the steel wire matrix.
[0007] During the cold drawing process of pearlite steel wire, plastic deformation and friction between the steel wire and the die will cause drawing temperature rise. Especially at high deformation rates, about 95% of the mechanical energy will be converted into heat energy, which means that the deformation rate can not only produce significant strain rate hardening but also cause significant drawing temperature rise. The effect of deformation rate on the mechanical properties of cold-drawn pearlite steel wire is often generally attributed to the carbon atoms produced by the decomposition of cementite interacting with dislocations under the action of drawing heat, causing the strength of the steel wire to increase and the plasticity to decrease. It is believed in the prior art that an increase in deformation rate is believed to accelerate the occurrence of dynamic strain aging and even cause the precipitation of intermediate carbides, which can easily lead to the occurrence of torsional delamination.
[0008] In summary, the vague understanding of the influence of deformation rate on the torsional performance of steel wire leads to the inability to reasonably control the deformation rate in the actual production process, and cannot solve the problem of torsional stratification of metal wires, which results in the torsional performance being unable to meet the requirements of engineering applications, seriously hindering the improvement of production efficiency.
[0009] Therefore, the present invention provides a torsion-free layered metal wire, which can be applied to bridge cable steel wires, automobile tire meridians, and diamond wire busbars for cutting photovoltaic silicon wafers. Summary of the invention
[0010] The purpose of the present invention is to provide a torsion-free layered metal wire and a preparation method thereof, wherein the metal wire can be applied to bridge cable steel wires, automobile tire meridians and diamond wire busbars for photovoltaic silicon wafer cutting.
[0011] This method aims to solve the problem in the prior art that metal wires are prone to torsional delamination, resulting in torsional performance that cannot meet engineering application requirements. The method provides a method for suppressing torsional delamination of metal wires by controlling the deformation rate. The above method is not only simple to operate, but also can effectively avoid torsional delamination by only controlling the cold drawing deformation rate.
[0012] To achieve the above object, the present invention is implemented by the following technical solutions:
[0013] A non-twisted layered metal wire, characterized in that:
[0014] The metal wire uses high carbon steel wire as raw material, the high carbon steel wire has a carbon content of 0.7wt.% ~1.20wt.%, a silicon content of 0.15wt.% ~ 0.50wt.%, a manganese content of 0.30wt.% ~ 0.60wt.%, a chromium content of 0.10wt.% ~ 0.30wt.%, a sulfur content not exceeding 0.010 wt.%, a phosphorus content not exceeding 0.010 wt.%, a copper content not exceeding 0.010 wt.%, an aluminum content not exceeding 0.010 wt., and the rest is iron content.
[0015] A method for preparing a non-twisted layered metal wire,
[0016] The method comprises the following preparation steps:
[0017] Step 1: Preprocessing
[0018] Select high carbon steel wire as raw material and carry out pre-treatment;
[0019] Step 2: Control the deformation rate e Preparation of cold drawn pearlite steel wire
[0020] (1) When the diameter of the steel wire after cold drawing (d) is 1mm≤d≤10mm, control e ≤6.0×10 1 s -1 and 3.0×10 2 s -1 ≤ e ≤1.0×10 3 s -1 , which can suppress torsional delamination;
[0021] (2) When d<1mm: control 1.0×10 3 s -1 < e <6.5×10 4 s -1 , which can suppress torsional delamination.
[0022] As a further improvement of this scheme,
[0023] When 1mm≤d≤10mm, cold drawing adopts dry multi-pass method and uses soap powder as lubricating medium;
[0024] When d<1mm, cold drawing is carried out by wet multi-pass method with emulsion for lubrication.
[0025] As a further improvement of this scheme,
[0026] The cold drawing deformation is ε, the single-pass elongation coefficient is μ, the drawing die half angle control is α, and the deformation rate is e, The pulling speed is ν;
[0027] Control ε≥1.5, 1<μ<1.2, 4°≤α≤8°, and then control by changing the drawing speed ν e By changing μ and α, e Make auxiliary adjustments.
[0028] As a further improvement of this scheme,
[0029] The high carbon steel wire has a carbon content of 0.7wt.% to 1.20wt.%, a sorbitization rate of ≥95% before cold drawing, a tensile strength of 1100MPa to 1600MPa, and a surface reduction rate of ≥35%. The structure is uniform and there is no decarburization or surface defects.
[0030] As a further improvement of this scheme,
[0031] When 1mm≤d≤10mm, the pretreatment process before cold drawing is sorbitizing heat treatment, pickling and boron coating or phosphating.
[0032] As a further improvement of this scheme,
[0033] In the austenitizing heat treatment, the austenitizing temperature is 850° C. to 1100° C. and the time is 20 s to 30 s. The isothermal quenching uses a sodium polyacrylate aqueous solution as a quenching agent with a concentration of 14±5%.
[0034] As a further improvement of this scheme,
[0035] The pickling process uses 200±10g / L hydrochloric acid solution at a temperature of 65±5℃; the borax content in the boron coating process is 4±2g / m 2 In the phosphating process, the weight of the phosphating film is 4±2g / m 2 .
[0036] As a further improvement of this scheme,
[0037] When d<1mm, the pretreatment process before cold drawing is sorbitizing heat treatment, alkali washing, pickling and electroplating brass coating.
[0038] As a further improvement of this scheme,
[0039] In the sorbitizing heat treatment, the austenitizing temperature is 850°C to 950°C, and the holding time is 15s to 20s; the isothermal quenching adopts a salt bath method, the temperature is 550°C to 650°C, and the holding time is 5 to 10s.
[0040] As a further improvement of this scheme,
[0041] The alkaline washing adopts a sodium hydroxide solution with a concentration of 120±10g / L and a temperature of 60±5°C; the acid washing adopts a hydrochloric acid solution with a concentration of 220±10g / L and a temperature of 68±5°C; the electroplated brass coating has a gram weight of not less than 12g / kg and a copper content of 65%~75%.
[0042] The preparation method of the method for suppressing the torsional delamination of metal wire by controlling the deformation rate of the present invention has the following beneficial effects:
[0043] 1) The present invention provides a torsion-free layered metal wire and a preparation method thereof, wherein the metal wire can be applied to bridge cable steel wires, automobile tire meridians, and diamond wire busbars for photovoltaic silicon wafer cutting.
[0044] 2) The present invention can effectively avoid torsional delamination by only controlling the cold drawing deformation rate. Compared with changing the raw material composition or even adding additional processes at the expense of other properties of the steel wire, the method of the present invention is simple to operate and easy to implement, and does not increase the difficulty of processing. The method of the invention can be widely used in bridge cable steel wires, automobile tire meridians, and diamond wire busbars for photovoltaic silicon wafer cutting, etc., and has the advantage of universality.
[0045] 3) The present invention can not only effectively suppress torsional delamination by controlling the cold drawing deformation rate, but also improve the production efficiency by at least 2.5 times. For example, within the deformation rate range that can effectively suppress torsional delamination as described in the present invention, for thick-gauge bridge cable steel wires, the production speed can be increased from 220m / min to 600m / min; for ultra-fine-gauge diamond wire busbars, the production speed can be increased from 240m / min to 630m / min.
[0046] 4) The cold drawing deformation rate in the present invention can be controlled by changing the cold drawing speed, wire diameter, single pass elongation coefficient, and wire drawing die half angle, mainly by changing ν e The change of μ and α can also be used to adjust the pull speed when the drawing speed is limited. e Auxiliary adjustments have the advantage of high operability dimension. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 : Cold drawn pearlite steel wire in Example 2 of the present invention ( e= 1.0×10 1 s -1 , d = 5mm) Microstructure of ferrite-cementite interface
[0048] Figure 2 : Cold drawn pearlite steel wire in Example 2 of the present invention ( e= 1.0×10 1 s -1 , d = 5mm) torsion angle-torque curve and torsion fracture morphology
[0049] Figure 3 : Cold drawn pearlite steel wire in the comparative example of the present invention ( e= 8.0×10 1 s -1 , d = 5mm) Microstructure of ferrite-cementite interface
[0050] Figure 4: Cold drawn pearlite steel wire in the comparative example of the present invention ( e= 8.0×10 1 s -1 , d = 5mm) torsion angle-torque curve and torsion layer morphology DETAILED DESCRIPTION
[0051] In order to make the purpose, technical solutions and advantages of the present invention more clear, the following embodiments and the accompanying drawings are combined to illustrate the present invention. Figures 1 to 4 The present invention will be further described:
[0052] The present invention provides a torsion-free layered metal wire. The metal wire uses high-carbon steel wire as a raw material. The high-carbon steel wire has a carbon content of 0.7wt.% to 1.20wt.%, a silicon content of 0.15wt.% to 0.50wt.%, a manganese content of 0.30wt.% to 0.60wt.%, a chromium content of 0.10wt.% to 0.30wt.%, a sulfur content of no more than 0.010 wt.%, a phosphorus content of no more than 0.010 wt.%, a copper content of no more than 0.010 wt.%, an aluminum content of no more than 0.010 wt., and the rest is iron content.
[0053] A method for preparing a twist-free layered metal wire of the present invention,
[0054] The specific process is as follows:
[0055] High carbon steel wire → pretreatment before cold drawing → cold drawing → wire winding.
[0056] The specific technical solutions are as follows:
[0057] Select high carbon steel wire with the required composition, structure and performance
[0058] The carbon content is 0.7wt.%~1.20wt.%, the sorbitization rate before cold drawing is not less than 95%, the tensile strength is 1100MPa~1600MPa, the area reduction rate is not less than 35%, the structure is uniform, and there is no decarburization and surface defects.
[0059] Pretreatment of high carbon steel wire before cold drawing
[0060] When 1mm≤d≤10mm, the specific process is austenitizing heat treatment, pickling and boron coating or phosphating. Among them, the austenitizing temperature in the austenitizing heat treatment is 850℃~1100℃, and the time is 20s~30s; the isothermal quenching uses sodium polyacrylate aqueous solution as the quenching agent with a concentration of 14±5%; the pickling uses 200±10g / L hydrochloric acid solution at a temperature of 65±5℃; the borax content in the boron coating process is 4±2g / m 2 In the phosphating process, the weight of the phosphating film is 4±2g / m 2 .
[0061] When d<1mm, the specific process is sorbitizing heat treatment, alkali washing, pickling and electroplating brass coating. Among them, the austenitizing temperature in sorbitizing heat treatment is 850℃~950℃, the time is 15s~20s; the isothermal quenching adopts salt bath method, the temperature is 550℃~650℃, and the holding time is 5~10s; the alkali washing adopts sodium hydroxide solution with a concentration of 120±10g / L and a temperature of 60±5℃; the pickling adopts hydrochloric acid solution with a concentration of 220±10g / L and a temperature of 68±5℃; the electroplating brass coating has a gram weight of not less than 12g / kg, and the copper content is 65%~75%.
[0062] 3) Cold drawing:
[0063] When 1mm≤d≤10mm, cold drawing adopts dry multi-pass method and uses soap powder as lubricating medium;
[0064] When d<1mm, cold drawing is done in wet multi-pass mode, using emulsion for lubrication. For pearlite steel wires of different diameters, the cold drawing deformation is controlled at ε≥1.5, the single-pass elongation coefficient is controlled at 1<μ<1.2, and the half angle of the wire drawing die is controlled at 4°≤α≤8°. The control is mainly achieved by changing ν. e The change of μ and α can also be e Make auxiliary adjustments.
[0065] Reel in the line.
[0066] In the non-twisted layered metal wire of the present invention, the main control requirements and mechanisms are as follows:
[0067] The reason why the present invention divides the diameter of the steel wire after cold drawing into two cases of 1mm≤d≤10mm and d<1mm and then controls the deformation rate respectively is that when 1mm≤d≤10mm, the cold-drawn pearlite steel wire usually adopts dry drawing, and when d<1mm, the cold-drawn pearlite steel wire usually adopts wet drawing. The latter has a significant inhibitory effect on the drawing temperature rise because it is better than the former, which is conducive to cold drawing of finer specification steel wires with higher deformation rates. In addition, there is a significant size effect in cold-drawn pearlite steel wires. For example, even under the same cold drawing conditions, large-sized wires are more likely to undergo torsional delamination than small-sized wires, and the difference in stress intensity factors between wires of different sizes is the main reason for the size effect (ISI J Int., 2001, 41 (2): 183-191). The deformation rate will affect the strain aging and stress intensity factor, so to inhibit torsional delamination, it is necessary to classify and control the deformation rate according to the diameter of the cold-drawn steel wire.
[0068] The reason why the present invention is to control when 1mm≤d≤10mm e ≤6.0×101 s -1 , because when e Not more than 6.0×10 1 s -1 When, with e Increase, the microstructure of cementite in cold drawn pearlite steel wire does not change significantly, and the cementite position is a mixed structure of amorphous cementite and a small amount of cementite nanocrystals. In this case, the dislocation movement in ferrite is hardly hindered. At the same time, the nanoscale amorphous interface can absorb dislocations, disperse stress concentration, and inhibit crack initiation. Therefore, the mixed structure of amorphous cementite and a small amount of cementite nanocrystals formed in cold drawn pearlite steel wire is beneficial to plastic deformation and can inhibit torsional delamination. The reason for controlling 3.0×10 2 s -1 ≤ e ≤1.0×10 3 s -1 This is because as the deformation rate increases further, the higher drawing temperature increases the cementite ordering degree, reduces the lattice defects, and significantly coarsens the cementite nanocrystals. Dislocations can bypass the coarsened cementite particles without being blocked, thus inhibiting torsional delamination, accompanied by a slight decrease in tensile strength. On the contrary, if 6.0×10 1 s -1 < e <3.0×10 2 s -1 ,along with e As the drawing temperature rises, the amorphous cementite in the cold-drawn pearlite steel wire gradually transforms into fine cementite nanocrystals. The cementite nanocrystals can effectively hinder the movement of dislocations during torsion, causing uneven plastic deformation and microcracks, which makes the steel wire prone to torsion delamination. At the same time, the pinning effect of cementite nanocrystals on dislocations will increase the tensile strength of the steel wire. In addition, for thick-gauge steel wire, the deformation rate reaches 1.0×10 3 s -1 , which means that it has reached the limit that the wire drawing equipment and molds can withstand.
[0069] The reason why the present invention controls 1.0×10 3 s -1 < e <6.5×10 4 s -1 , because e In this range, the cementite in the cold drawn pearlite steel wire is mainly amorphous cementite and a small amount of cementite nanocrystals, which is different from the case of 1mm≤d≤10mm. e Not more than 6.0×10 1 s -1The situation is similar to that of the case where torsion delamination can be suppressed. At the same time, the ordering degree of amorphous cementite is improved under the action of the pull-out temperature rise, resulting in a slight increase in tensile strength. However, once e More than 6.5×10 4 s -1 When the deformation rate is very high, adiabatic shearing is likely to occur, resulting in local temperature rise and severe plastic deformation, which will cause a sharp deterioration in the torsional performance and tensile strength of the steel wire. e Reach 6.5×10 4 s -1 , the steel wire is close to the deformation capacity limit and also close to the capacity limit of industrial wire drawing equipment.
[0070] The reason why the present invention controls the cold drawing deformation at ε≥1.5 is to ensure that the cementite can undergo obvious deformation and a certain degree of decomposition during the cold drawing process to form amorphous cementite. The single-pass elongation coefficient is controlled at 1<μ<1.2 to make the pearlite steel wire deform evenly during the cold drawing process, while an excessively large elongation coefficient will cause uneven deformation of the steel wire and affect the torsional performance of the steel wire. The half angle of the wire drawing die is controlled at 4°≤α≤8° because a die half angle lower than 4° will increase friction resistance, which is particularly prone to wire breakage for fine-gauge steel wires and also increases die loss; if the die half angle is set too large, it will cause inconsistent deformation of the core and edge of the steel wire, causing the so-called "center burr", which will seriously deteriorate the torsional performance of the steel wire. Example 1
[0071] 1) Control the deformation rate to 4.0×10 -1 s -1 Preparation of cold drawn pearlite steel wire with a diameter of 5 mm
[0072] Select high carbon steel wire: diameter 12.5mm, carbon content 0.82wt.%, troostitization rate before cold drawing is 95%, tensile strength is 1150MPa, area reduction rate is 40%, structure is uniform, and there is no decarburization and surface defects.
[0073] 2) Pretreatment of high carbon steel wire before cold drawing: austenitizing temperature in the sorbitizing heat treatment is 950℃, and the time is 30s; sodium polyacrylate aqueous solution is used as quenching agent in isothermal quenching, and the concentration is 14%; 200g / L hydrochloric acid solution is used for pickling, and the temperature is 65℃; the borax content in the boron coating process is 4g / m 2 In the phosphating process, the weight of the phosphating film is 4g / m 2 .
[0074] 3) Cold drawing: Cold drawing adopts dry multi-pass method, using soap powder as lubricating medium; cold drawing deformation ε=1.8, single-pass elongation coefficient μ=1.1, wire drawing die half angle α=8°, drawing speed ν=0.3m / min. The prepared cold-drawn pearlite steel wire has no torsion delamination phenomenon, the torsion angle is 7450°, and the tensile strength is about 1840MPa.
[0075] 4) Reel in the line. Example 2
[0076] 1) Control the deformation rate to 1.0×10 1 s -1 Preparation of cold drawn pearlite steel wire with a diameter of 5 mm
[0077] Select high carbon steel wire: diameter 12.5mm, carbon content 0.82wt.%, troostitization rate before cold drawing is 95%, tensile strength is 1150MPa, area reduction rate is 40%, structure is uniform, and there is no decarburization and surface defects.
[0078] 2) Pretreatment of high carbon steel wire before cold drawing: austenitizing temperature in the sorbitizing heat treatment is 950℃, and the time is 30s; sodium polyacrylate aqueous solution is used as quenching agent in isothermal quenching, and the concentration is 14%; 200g / L hydrochloric acid solution is used for pickling, and the temperature is 65℃; the borax content in the boron coating process is 4g / m 2 In the phosphating process, the weight of the phosphating film is 4g / m 2 .
[0079] 3) Cold drawing: Cold drawing adopts dry multi-pass method, using soap powder as lubricating medium; cold drawing deformation ε=1.8, single-pass elongation coefficient μ=1.1, wire drawing die half angle α=8°, drawing speed ν=7.2m / min. The ferrite-cementite micro-interface in the prepared cold-drawn pearlite steel wire is as follows: Figure 1 As shown in the figure, the cementite position is a mixed structure of amorphous cementite and a small amount of cementite nanocrystals. The prepared cold-drawn pearlite steel wire has no torsion delamination phenomenon, the torsion angle is about 7300°, and the torsion fracture is also a typical flush fracture, such as Figure 2 As shown in Figure 2, the tensile strength of the prepared cold-drawn pearlite steel wire is about 1860 MPa.
[0080] 4) Reel in the line. Example 3
[0081] 1) Control the deformation rate to 4.0×10 2 s -1 Preparation of cold drawn pearlite steel wire with a diameter of 5 mm
[0082] Select high carbon steel wire: diameter 12.5mm, carbon content 0.82wt.%, troostitization rate before cold drawing is 95%, tensile strength is 1150MPa, area reduction rate is 40%, structure is uniform, and there is no decarburization and surface defects.
[0083] 2) Pretreatment of high carbon steel wire before cold drawing: austenitizing temperature in the sorbitizing heat treatment is 950℃, and the time is 20s; sodium polyacrylate aqueous solution is used as quenching agent for isothermal quenching, and the concentration is 14%; 200g / L hydrochloric acid solution is used for pickling, and the temperature is 65℃; the borax content in the boron coating process is 4g / m 2 In the phosphating process, the weight of the phosphating film is 4g / m 2 .
[0084] 3) Cold drawing: Cold drawing adopts dry multi-pass method, using soap powder as lubricating medium; cold drawing deformation ε=1.8, single-pass elongation coefficient μ=1.1, wire drawing die half angle α=8°, drawing speed ν=300m / min. The prepared cold-drawn pearlite steel wire has no torsion delamination phenomenon, the torsion angle is about 7400°, and the tensile strength is about 1866MPa.
[0085] 4) Reel in the line. Example 4
[0086] 1) Control the deformation rate to 2.5×10 4 s -1 Preparation of cold drawn pearlite steel wire with a diameter of 40 μm
[0087] Select high carbon steel wire: diameter 0.47mm, carbon content 0.92wt.%, troostitization rate before cold drawing 96%, tensile strength 1420MPa, area reduction rate 45%, uniform structure, no decarburization and surface defects.
[0088] 2) Pretreatment of high carbon steel wire before cold drawing: austenitizing temperature in sorbitizing heat treatment is 880℃, time is 18s; isothermal quenching adopts salt bath method, temperature is 580℃, holding time is 8s; alkali washing adopts sodium hydroxide solution with concentration of 120g / L, temperature is 60℃; pickling adopts hydrochloric acid solution with concentration of 220g / L, temperature is 68℃; electroplated brass coating weight is 13g / kg, copper content is 71%.
[0089] 3) Cold drawing: Cold drawing adopts dry multi-pass method, using soap powder as lubricating medium; cold drawing deformation ε=4.9, single-pass elongation coefficient μ=1.05, wire drawing die half angle α=4°, drawing speed ν=240m / min. The prepared cold-drawn pearlite steel wire has no torsion delamination phenomenon, the number of torsion circles is about 35 circles (torsion test standard: gauge length 100mm, rotation speed 1r / s, load 0.5kg), and the tensile strength is about 4720MPa.
[0090] 4) Reel in the line. Example 5
[0091] 1) Control the deformation rate to 6.3×10 4 s -1 Preparation of cold drawn pearlite steel wire with a diameter of 40 μm
[0092] Select high carbon steel wire: diameter 0.47mm, carbon content 0.92wt.%, troostitization rate before cold drawing 96%, tensile strength 1420MPa, area reduction rate 45%, uniform structure, no decarburization and surface defects.
[0093] 2) Pretreatment of high carbon steel wire before cold drawing: austenitizing temperature in sorbitizing heat treatment is 880℃, time is 18s; isothermal quenching adopts salt bath method, temperature is 580℃, holding time is 8s; alkali washing adopts sodium hydroxide solution with concentration of 120g / L, temperature is 60℃; pickling adopts hydrochloric acid solution with concentration of 220g / L, temperature is 68℃; electroplated brass coating weight is 13g / kg, copper content is 71%.
[0094] 3) Cold drawing: Cold drawing adopts dry multi-pass method, using soap powder as lubricating medium; cold drawing deformation ε=4.9, single-pass elongation coefficient μ=1.05, wire drawing die half angle α=4°, drawing speed ν=600m / min. The prepared cold-drawn pearlite steel wire has no torsion delamination phenomenon, the number of torsion circles is about 33 circles (torsion test standard: gauge length 100mm, rotation speed 1r / s, load 0.5kg), and the tensile strength is about 4706MPa.
[0095] 4) Reel in the line.
[0096] Comparative Example
[0097] The same as Example 1, Example 2 and Example 3, except that the cold drawing deformation rate is controlled to 8.0×10 1 s -1 .
[0098] Comparative results analysis:
[0099] The ferrite-cementite micro-interface in the prepared cold-drawn pearlite steel wire, such as Figure 3As shown in the figure, the amorphous cementite at the cementite position gradually transforms into many fine cementite nanocrystals. The prepared cold-drawn pearlite steel wire shows torsion stratification, and the torsion angle is only 4150°, as shown in the figure. Figure 4 As shown. The tensile strength of the prepared cold-drawn pearlite steel wire is about 2010MPa. As can be seen from Table 1, no torsional delamination phenomenon occurs under the deformation rate conditions controlled by Examples 1 to 3, while the deformation rate in the comparative example is 8.0×10 1 s -1 By comparing the organizational characteristics under the above different deformation rates, it can be found that by controlling the deformation rate to prevent the cold-drawn pearlite steel wire from appearing fine cementite nanocrystals, the torsional delamination can be effectively suppressed. In addition, by comparing Examples 1 to 3, it can be found that there is no significant difference in torsional performance and tensile strength among the three, which means that by controlling the deformation rate, a significant improvement in production efficiency can be achieved without sacrificing torsional performance and tensile strength.
[0100] Table 1 Comparison of the organization and performance of Examples 1 to 3 and the comparative example
[0101] <![CDATA[Deformation rate (s -1 )]]> Organizational characteristics Torsion characteristics Torsion angle (°) Tensile strength(MPa) Example 1 <![CDATA[4.0×10 -1 ]]> The cementite region is mainly composed of amorphous cementite No stratification 7450 1840 Example 2 <![CDATA[1.0×10 1 ]]> The cementite region is mainly composed of amorphous cementite, and the degree of ordering has been improved. No stratification 7300 1860 Example 3 <![CDATA[4.0×10 2 ]]> Cementite nanograin coarsening No stratification 7400 1866 Comparative Example <![CDATA[8.0×10 1 ]]> The cementite region is mainly composed of cementite nanocrystals Layered 4150 2010
[0102] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent changes made using the present invention are within the patent protection scope of the present invention.
Claims
1. A method for preparing a non-twisted layered metal wire, characterized in that: The metal wire material is made of high carbon steel wire, wherein the carbon content of the high carbon steel wire is 0.7wt.% to 1.20wt.%, the silicon content is 0.15wt.% to 0.50wt.%, the manganese content is 0.30wt.% to 0.60wt.%, the chromium content is 0.10wt.% to 0.30wt.%, the sulfur content does not exceed 0.010 wt.%, the phosphorus content does not exceed 0.010 wt.%, the copper content does not exceed 0.010wt.%, the aluminum content does not exceed 0.010 wt.%, and the rest is iron content; The method comprises the following preparation steps: Step 1: Preprocessing Select high carbon steel wire as raw material and carry out pretreatment; Step 2 Cold drawing: by controlling the deformation rate e Preparation of cold drawn pearlitic steel wire; When the wire diameter (d) after cold drawing is 1 mm ≤ d ≤ 10 mm, control e ≤ 6.0×10 1 s -1 or 3.0×10 2 s -1 ≤ e ≤ 1.0×10 3 s -1 ; When d < 1 mm: control 1.0×10 3 s -1 < e < 6.5×10 4 s -1 ; When 1 mm ≤ d ≤ 10 mm, cold drawing is carried out using a dry multi-pass method, using soap powder as the lubricating medium; When d < 1 mm, cold drawing is done by wet multi-pass method with emulsion lubrication; The cold drawing deformation is ε, the single-pass elongation coefficient is μ, the drawing die half angle control is α, and the deformation rate is e, The pulling speed is ν; Control ε ≥ 1.5, 1 < μ < 1.2, 4° ≤ α ≤ 8°, and then control the e By changing μ and α, e Make auxiliary adjustments.
2. The method for twisting-free layered metal wire according to claim 1, characterized in that: The high carbon steel wire has a carbon content of 0.7wt.% to 1.20wt.%, a troostitization rate before cold drawing of ≥95%, a tensile strength of 1100 MPa to 1600 MPa, and an area reduction rate of ≥35%.
3. The method for twisting-free layered metal wire according to claim 1, characterized in that: When 1 mm ≤ d ≤ 10 mm, the pretreatment process before cold drawing is sorbitizing heat treatment, pickling and boron coating or phosphating.
4. The method for twisting-free layered metal wire according to claim 3, characterized in that: The austenitizing temperature in the austenitizing heat treatment is 850°C to 1100°C, and the time is 20 s to 30 s; the isothermal quenching uses a sodium polyacrylate aqueous solution as a quenching agent, and the concentration is 14 ± 5%; The pickling process uses a 200 ± 10 g / L hydrochloric acid solution at a temperature of 65 ± 5 °C; the borax content in the boron coating process is 4 ± 2 g / m 2 The weight of the phosphating film in the phosphating process is 4 ± 2 g / m 2 .
5. The method for twisting-free layered metal wire according to claim 1, characterized in that: When d < 1 mm, the pretreatment process before cold drawing is sorbitizing heat treatment, alkali washing, pickling and electroplating brass coating.
6. The method for twisting-free layered metal wire according to claim 5, characterized in that: In the sorbitizing heat treatment, the austenitizing temperature is 850°C to 950°C, and the holding time is 15 s to 20 s; the isothermal quenching adopts a salt bath method, the temperature is 550°C to 650°C, and the holding time is 5 to 10 s.
7. The method for twisting-free layered metal wire according to claim 5, characterized in that: The alkaline washing adopts a sodium hydroxide solution with a concentration of 120 ± 10 g / L and a temperature of 60 ± 5 °C; the acid washing adopts a hydrochloric acid solution with a concentration of 220 ± 10 g / L and a temperature of 68 ± 5 °C; the electroplated brass coating has a gram weight of not less than 12 g / kg and a copper content of 65% to 75%.
Citation Information
Patent Citations
Preparation Method of Super High Strength Steel Wire with Anti-Torsion Lamination and Excellent Fatigue Performance
CN103785704B
A method for strengthening a high-strength bead wire material and a method for preparing a bead wire
CN105483556B
Production method of high-strength and high-torsion zinc-coated steel wire for bridge cable rope
CN106111726A
Wire, steel wire and methods for manufacturing wire
CN102292460A
Steel wire including excellent torsional properties and manufacturing method thereof
KR1020140009883A